THE INFLUENCE OF PUBLIC PARTICIPATION ON SUSTAINABLE TRANSPORTATION AND REGIONAL DEVELOPMENT IN MEDAN - Hairulsyah Hairulsyah (Faculty of Geography, Universitas Gadjah Mada, 2013)
Sustainable transportation becomes very important in a certain town since it can influence thedevelopment of the town itself. One of the sustainable transportations is angkot (urban publictransportation). Urban public transportation is one of the means of land transportation whichis mostly used in big towns in Indonesia, including Medan. The aim of the study was toanalyze the influence of public participation on sustainable transportation and regionaldevelopment in Medan. There were 400 respondents who used urban public transportation inMedan. They were divided proportionally into 21 sub-districts in Medan. The data wereanalyzed by using Structural Equation Modeling (SEM) with an AMOS version 18 program.The hypothetical test was obtained by seeing the probability value or by seeing thesignificance of the correlation of each variable such as public participation, sustainabletransportation, and regional development. The result of the study showed that there was theinfluence of public participation on sustainable transportation and regional development inMedan. Public participation could also directly influence regional development in Medan.